The secret of Sarah Revere - Rinaldi, Ann. (San Diego : Gulliver Books/Harcourt Brace, 1995)
Paul Revere's daughter describes her father's "rides" and the intelligence network of the patriot community prior to the American Revolution.
Includes bibliographical references (p. 319-320).
530
Accelerated Reader AR
Keywords: Revere, Paul, -- 1735-1818 -- Juvenile fiction; Revere, Paul, -- 1735-1818 -- Fiction; Spies -- Fiction; Historical fiction; Silversmiths -- Fiction; Fathers and daughters -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction